2016
DOI: 10.1007/s11064-016-1919-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Chlorogenic Acid and its Metabolites on Hydrogen Peroxide-Induced Alterations in Rat Brain Slices: A Comparative Study with Resveratrol

Abstract: The effectiveness of chlorogenic acid and its main metabolites, caffeic and quinic acids, against oxidative stress was investigated. Resveratrol, another natural phenolic compound, was also tested for comparison. Rat cortical slices were incubated with 200 μM H2O2 for 1 h, and alterations in oxidative stress parameters, such as 2, 3, 5-triphenyltetrazolium chloride (TTC) staining and the production of both malondialdehyde (MDA) and reactive oxygen species (ROS), were assayed in the absence or presence of pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…The peroxynitrite is capable of initiating lipid peroxidation, inflammation, cancer, and other pathological condition (Bates, Baker, Guerra, & Harrison, ). The observed results from this finding also agree with other studies on the inhibitory effects of caffeic acid and chlorogenic acid on MDA level and their anti‐inflammatory effects during wound healing in experimental animals (Bagdas et al, ; Gul, Demircan, Bagdas, & Buyukuysal, ). Furthermore, as revealed in Figure , caffeic and chlorogenic acid also exhibit NO radical scavenging ability, which can prevent peroxynitrite formation, reduce the potential for lipid peroxidation in the heart, and protect the heart membrane integrity.…”
Section: Discussionsupporting
confidence: 92%
“…The peroxynitrite is capable of initiating lipid peroxidation, inflammation, cancer, and other pathological condition (Bates, Baker, Guerra, & Harrison, ). The observed results from this finding also agree with other studies on the inhibitory effects of caffeic acid and chlorogenic acid on MDA level and their anti‐inflammatory effects during wound healing in experimental animals (Bagdas et al, ; Gul, Demircan, Bagdas, & Buyukuysal, ). Furthermore, as revealed in Figure , caffeic and chlorogenic acid also exhibit NO radical scavenging ability, which can prevent peroxynitrite formation, reduce the potential for lipid peroxidation in the heart, and protect the heart membrane integrity.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is tempting to suggest that exogenous administration of antioxidants should be investigated as a potential approach to protect cells against ROS for the treatment of osteoporosis. Previous studies have revealed the antioxidant effect of CGA, effectively scavenging free radicals and inhibiting lipid peroxidation [25, 30, 31]. Recent report demonstrated that CGA efficiently inhibits osteoblast apoptosis and ameliorates hormone-induced femoral head necrosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…amelioration of the decrease of MDA and ROS levels in rat cortical slices after the H 2 O 2 -induced oxidative stress [43]. …”
Section: Figurementioning
confidence: 99%